Investigating the Relationship between Cognitive Distortion and Fear of Negative Evaluation with the Quality of Marital Relationships of Female Teachers in Taibad Schools - Zeinab Jalambadani (Beyhagh)
Background and Aims: The purpose of the present study was to investigate the relationship between cognitive distortion and fear of negative evaluation with the quality of marital relationships of female teachers in Taibad schools in 1402. Materials and Methods: The descriptive-correlation research method was cross-sectional and the statistical population was 330 married female teachers of Taibad city in the academic year of 1402-1401, who were selected by targeted and accessible sampling method. Research tools were Abdullahzadeh Vesalar's Cognitive Distortion Questionnaire (1389), Lori's Fear of Negative Evaluation (1983) and Busby, Karan, Larsen and Christensen's Quality of Marital Relationship Questionnaire (1995). Pearson regression correlation coefficient test was used for data analysis using spss24 statistical software. Result: The results showed that there is a statistically significant relationship between cognitive distortion and fear of negative evaluation with the quality of teachers' marital relationships. There is a statistically significant positive relationship between cognitive distortion and the quality of teachers' marital relationships, and this correlation is significant for the components of cognitive distortion (the higher the cognitive distortion score, the more appropriate thinking a person has). There is a statistically significant positive relationship between the fear of negative evaluation and the quality of teachers' marital relationships. Conclusion: The results showed that cognitive distortion and fear of negative evaluation can predict the quality of teachers' marital relationships